Blastic plasmacytoid dendritic cell neoplasm secondary to acute myeloid leukemia with shared mutations in TET2 and DNMT3A: a case report and literature review - Sun, Yao; Liu, Yingjie; Liu, Na; Zhang, Xiaohui; Huang, Wenrong; Hu, Liangding (Frontiers in Immunology, 2025)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare and aggressive hematologic malignancy. Recent studies have highlighted its occurrence in patients with a history of preceding myeloid neoplasms. This case report describes a patient who developed BPDCN secondary to acute myeloid leukemia (AML), with bone marrow involvement and clinical signs suggestive of CNS involvement. Genetic analysis revealed mutations in JAK2, DNMT3A, TET2, IKZF1, and MPL in BPDCN. Notably, TET2 and DNMT3A mutations were also present in the initial AML. A comprehensive review of existing literature identified 10 patients with BPDCN who had prior or concurrent hematologic malignancies, with detailed clonal data documented for each case. Among these, TET2 mutations emerged as a common feature, present in BPDCN and the associated hematologic malignancies in 9 of the 10 patients. Additionally, some of these patients exhibited early hematopoietic clones, diagnosed with lymphoma or secondary AML, with TET2 mutations consistently detected across all these conditions. These observations highlight the critical role of TET2 mutations in the development and progression of BPDCN and related hematologic neoplasms. However, the hierarchical structure of clonal evolution remains unclear, so this report also discusses the potential clonal relationships between different tumors.